2013
DOI: 10.1074/jbc.m113.487322
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Processing by Human 8-Oxoguanine-DNA Glycosylase Mutants with the Occluded Active Site

Abstract: Background: Oxoguanine-DNA glycosylase (OGG1) removes highly mutagenic 8-oxoguanine from DNA. Results: OGG1 mutations C253I and C253L occlude the active site and distort the OGG1-DNA precatalytic complex but retain some activity. Conclusion: Active site of OGG1 possesses flexibility that partially compensates for distortions. Significance: Active site plasticity may be important for dynamic recognition of multiple DNA lesions by DNA glycosylases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…Our data suggest that although Gly42 provides the sole interaction that structurally discriminates 8-oxoG and G in the active site, it may be strong enough to keep G from entering the active site as deeply as does 8-oxoG (Figure 10C). Experimental studies have shown that the Gln315Phe, Gln315Trp, Cys253Ile, and Cys253Leu mutations, which perturb the active site disposition of 8-oxoG but not expel it altogether, can severely reduce the catalytic activity of OGG1, 16, 44 thus suggesting that the catalysis of base excision by OGG1 requires very precise positioning of the reacting moieties. Therefore, the unfavorable interaction of Gly42 may prevent G from achieving the optimal position for catalysis, and thus the active site geometry constitutes the final damage checkpoint of OGG1.…”
Section: Resultsmentioning
confidence: 99%
“…Our data suggest that although Gly42 provides the sole interaction that structurally discriminates 8-oxoG and G in the active site, it may be strong enough to keep G from entering the active site as deeply as does 8-oxoG (Figure 10C). Experimental studies have shown that the Gln315Phe, Gln315Trp, Cys253Ile, and Cys253Leu mutations, which perturb the active site disposition of 8-oxoG but not expel it altogether, can severely reduce the catalytic activity of OGG1, 16, 44 thus suggesting that the catalysis of base excision by OGG1 requires very precise positioning of the reacting moieties. Therefore, the unfavorable interaction of Gly42 may prevent G from achieving the optimal position for catalysis, and thus the active site geometry constitutes the final damage checkpoint of OGG1.…”
Section: Resultsmentioning
confidence: 99%
“…Lukina et al [ 50 ] engineered C253L and C253I mutant hOGG1 forms with an occluded active site pocket by replacement of a Cys253 to a bulky leucine or isoleucine. Despite the perturbed active site geometry afforded by this mutation and dramatic decline in catalytic activity, the enzyme was still catalytically active.…”
Section: Recognition Of 8-oxogmentioning
confidence: 99%
“…The Watson-Crick edge is recognized by Gln315 through two direct hydrogen bonds and a water bridge. Replacement of Cys253 or Gln315 with bulkier side chains strongly interferes with oxoG excision but affects the abasic site site cleavage to a much lower degree [121,122]. Given that the electric dipoles of G and oxoG are almost opposite, and that 7-deazaguanine and 7-deaza-8-azaguanine cannot form bonds to Gly42 but still efficiently enter the active site [120], it seems that stabilization of oxoG in the active site pocket is not limited to hydrogen bonding but to a significant degree relies on hydrophobic and electrostatic interactions with the enzyme.…”
Section: Ogg1mentioning
confidence: 99%
“…An extended series of structures of Fpg [102][103][104][105][127][128][129][130][131] and OGG1 [110,120,121,123,[132][133][134][135][136][137][138], together with molecular dynamic simulation of conformational transition between these intermediates [139][140][141][142], and stopped-flow studies [115,122,140,[143][144][145][146][147][148][149][150] produced a multistep oxoG recognition model that turned out to be surprisingly similar for these two enzymes despite their structural dissimilarity. Both Fpg and OGG1 kink DNA by 40 • -50 • and insert an aromatic wedge (Phe or Tyr) into the base stack, causing the sampled base pair to buckle.…”
Section: Dynamic Oxog Recognitionmentioning
confidence: 99%